Mast cells are associated with exacerbations and eosinophilia in children with severe asthma. Issue 5 (6th October 2016) - Lezmi, Guillaume; Galmiche-Rolland, Louise; Rioux, Sabine; Jaubert, Francis; Tillie-Leblond, Isabelle; Scheinmann, Pierre; Gosset, Philippe; de Blic, Jacques
The role of mast cells in the pathogenesis of childhood asthma is poorly understood. We aimed to estimate the implication of airway mucosal mast cells in severe asthma and their relationship with clinical, functional, inflammatory and remodelling parameters. Bronchial biopsies were performed in 36 children (5–18 years) with severe asthma: 24 had frequent severe exacerbations and/or daily symptoms in the previous year (symptomatic group), and 12 had few symptoms and a persistent obstructive pattern (paucisymptomatic group). Nine children without asthma were included as control subjects. We assessed mast cells in the submucosa and airway smooth muscle using c-kit antibodies and in the entire biopsy area using Giemsa. The number of submucosal mast cells was higher in the symptomatic group than in the paucisymptomatic group (p=0.02). The number of submucosal mast cells correlated with the number of severe exacerbations (p=0.02, r=0.37). There were positive correlations between the number of submucosal mast cells (p<0.01, r=0.44), airway smooth muscle mast cells (p=0.02, r= 0.40), mast cells stained by Giemsa (p<0.01, r=0.44) and submucosal eosinophils. Mast cells are associated with severe exacerbations and submucosal eosinophilic inflammation in children with severe asthma. Submucosal mast cells are associated with exacerbations and submucosal eosinophilia in children with severe asthma http://ow.ly/uwly302J5mE